Perivascular Adipose Tissue Oxidative Stress on the Pathophysiology of Cardiometabolic Diseases - Victorio, Jamaira A.; Davel, Ana P. (Current Hypertension Reviews, 2020)
Most of the systemic blood vessels are surrounded by the perivascular adipose tissue (PVAT). Healthy PVAT is anticontractile and anti-inflammatory, but a dysfunctional PVAT has been suggested to link cardiometabolic risk factors to vascular dysfunction. Vascular oxidative stress is an important pathophysiological event in cardiometabolic complications of obesity, type 2 diabetes, and hypertension. PVAT-derived adipocytes generate reactive oxygen species (ROS) including superoxide anion and hydrogen peroxide that might signal to the vascular wall. Therefore, an abnormal generation of ROS by PVAT emerges as a potential pathophysiological mechanism underlying vascular injury. This review summarizes new findings describing ROS production in the PVAT of several vascular beds, major sources of ROS in this tissue including mitochondria, NADPH oxidase and eNOS uncoupled, and finally, changes in ROS production affecting vascular function in the presence of cardiometabolic risk factors and diseases.
Keywords: cardiometabolic diseases